Identifying barriers to the educational role of midwives in Cyprus and defining determinants in behaviour terms using the Behaviour Change Wheel: a mixed-method formative study - Nicos Middleton; Eleni Hadjigeorgiou; Ourania Kolokotroni; Veronika Christodoulides; Ioanna Koliandri; Christiana Nicolaou; Maria Papadopoulou; Christiana Kouta; Maria Karanikola; Alison Baum; the Baby Buddy Forward team (BMC, 2022)
Abstract Background Τhe Baby Buddy Cyprus webapp was co-created with parents and health professionals within a Participatory Action Research framework. While using Baby Buddy in routine consultations can support the educational role of mother-child healthcare providers (HP), antenatal education (AE) may be currently perceived as a formal activity within the physical space of the antenatal class. We aimed to gain an understanding of influences on midwives engaging in an educational role during routine appointments and identify potential interventions using the Behaviour Change Wheel (BCW) framework. Methods This is a formative mixed-methods research study, with a convergent parallel design, guided by the COM-B model and related Theoretical Domains Framework (TDF). Complimentary methods were used to collect information from in-training and registered midwives: focus group (N = 11), questionnaire survey (N = 24) and Nominal Group Technique during workshops (N = 40). Deductive content analysis of qualitative data and quantitative survey analysis shaped the behaviour diagnosis along the 6 COM-B and 14 TDF domains, and informed the selection of relevant intervention functions and related Behaviour Change Techniques from the BCW taxonomy. Results AE is viewed as a core function of the professional role, yet neither supported nor prioritized by current practices. Problematic areas relate to organizational context, such as weak interprofessional collaboration and lack of policy, protocols and resources. In addition, medicalization of birth and related socio-cultural norms, pertaining to users and providers, are sustaining alienation of the midwife and conditions of power dynamics. AE was perceived as a means to enhance the autonomy of the profession but there might be issues with procedural knowledge and the need for skill development was identified. Several intervention functions were identified as promising, however cognitive re-framing through strategic communication and modelling may also be needed both in terms of providing "credible models" for the role itself as well as re-framing AE through the concept of "making every contact count". Conclusions AE is currently perceived to be a 'bad fit' with routine practice. The study identified several barriers to the educational role of midwives, influencing Capacity, Opportunity and Motivation. While digital tools, such as Baby Buddy, can facilitate aspects of the process, a much wider behaviour and system change intervention is needed to enhance midwives' educational role and professional identity. In addition to proposing a theory-driven research-informed intervention, the process functioned as a participatory learning experience through collective reflection.